A finite-difference method for solving initial-boundary value problems for loaded differential and integro-differential equations - Bondarev, E. A.; Voevodin, A. F. (Differential equations, 2000)
(ProQuest: Abstract omitted; see image)[PUBLICATION ABSTRACT]